Photoinduced Stereoselective Giese Addition on Coumarins - Singh, Shashank; Singh, Ravi P. (Synthesis, 2024)
Diastereoselective Giese addition on coumarin-3-carboxylate bearing a chiral auxiliary with N-hydroxyphthalimide ester to generate the corresponding alkylated adduct has been explored. Among screened chiral auxiliaries, bulkier one with appropriate steric hindrance is better for diastereoselective addition. Mechanistic studies involving fluorescence studies and On/Off experiments shed insight onto the plausible reaction pathway.
Keywords: diastereoselectivity; coumarin-3-carboxylate; (+)-phenylmenthol; N-hydroxyphthalimide ester; Eosin Y